Financial Analysis of E.ON UK, comparison with the main competitors in the UK Utility sector. - Maciuk, Aneta (2009)
The purpose of this report is to analyse the financial condition of E.ON UK and compare it to its four biggest direct competitors (Centrica/British Gas, EDF, SSE, RWE) on the UK Utilities scene. We analysed the financial statements for the last five-year period (2004-2008). Methods of analysis include trend, horizontal and vertical analyses as well as profitability, liquidity, financial and investment ratios. Results of data analysed show that E.ON financial position is exactly in the middle, between the best and worst performers. E.ON can be considered as a leader when looking at the financial strength ratios (reasonable gearing and high interest cover) however its performance could be improved in profitability and liquidity. The major areas of weakness require further investigation and remedial action by management. Recommendations discussed include: